Vaccination Against SARS-CoV-2 in Lung Transplant Recipients: Immunogenicity, Efficacy and Safety - Svorcova, Monika; Novysedlak, Rene; Lischke, Robert; Vachtenheim, Jiri; Strizova, Zuzana (Frontiers in Immunology, 2022)
Lung transplant (LuTx) recipients are considered to be at higher risk of developing serious illness from COVID-19. COVID-19 vaccines were shown randomized clinical trials to substantially reduce the severity of COVID-19, however, patients receiving immunosuppressants were excluded from these trials. Observational studies report a proportion of solid organ transplant (SOT) recipients being able to mount sufficient titres of SARS-CoV-2 specific IgG antibodies, however, other studies demonstrate that more than 90% of the SOT recipients elicit neither humoral nor cellular immune response after vaccination. Currently, the third booster dose of the COVID-19 vaccines was shown to elicit strong immune responses and may, thus, represent a potent tool in the prevention of severe COVID-19 infection in SOT recipients, including patients after lung transplantation. To address the main challenges of SARS-CoV-2 vaccination in LuTx recipients in the era of COVID-19, we have closely collected all available data on the immunogenicity, efficacy and safety of COVID-19 vaccines in LuTx recipients.